Reliability - safety set of structures - Huynh, Le Xuan; Binh, Do Van (Vietnam Journal of Mechanics, 2001)
Based on the results of A. D. Rzanitsin and V. D. Raizer in the references of [1] and [2], this paper gives other definitions of the confidence level of subjected loads βs and the confidence level of the strength of materials βR, then studies the relationship between the load factor k, the material factor m and the safety factor n in the traditional models with the factors of βs, βR and βs in the random models in the structural design. The research results show that physical meaning of two factors of βs, βR is the same as the factors of k and m, however it gives more clearly assessments on effects of the over load state and the material inhomogeneous state of the safety working state of the structures. Since the reliability - safety set is also determined from the research results. Some numerical examples are carried out to show the relationship between these above factors.